Making Peace With History: Post-Conflict Teachers’ Experiences In Aceh - Muhammad Munadi; Rosalia Sari (STAI Hubbulwathan Duri, 2022)
This research aimed to determine the implementation of peace education through history subjects and the development of historical materials for the development of national unity and peace. The research used the descriptive qualitative research method. The research subjects were teachers of history and students of class XII IPA 2 MAN 1 Banda Aceh. The research informants were teachers of non-history subjects and the principal of MAN 1 Banda Aceh. The validity of this research data used triangulation. The data analysis used the Miles and Huberman model: data reduction, data display, and conclusion verification data. The results showed that peace education through history learning was not carried out in classrooms but made use of the Aceh Peace Memorial Room. This room made it easier for students to directly access the events of the Aceh conflict and the peace process. This condition made it easier for students to directly understand the material on Overcoming the Threat of National Disintegration and its relation to peace in Aceh. In the early stages, the students toured the Aceh peace memorial room. They saw photos of Aceh's conflict and peace journey. After the tour, they continued to see two movies about ‘Weaving Peace in Aceh’ and ‘Sustainability and Example of Aceh Peace’. Students reflected on these three activities by writing articles themed Aceh Peace Strengthens National Integration. The results of this paper were recorded as student work entitled ‘Aceh Peace Strengthens National Integration’ in which there were subtitles from student groups.